Laying hen feces for ruminant feeds microbiological analyses - Iturrino, Rubén Pablo Schocken; de Freitas, Júlio Cesar Mestriner; Sampaio, Alexandre Amstalden Moraes; Sampaio, Margaret Aparecida P. Moraes (Pesquisa Agropecuaria Brasileira, 1992)
The objectives of the present study were to evaluate the variation in total number of microorganisms in laying hen fecal samples and to identify the pathogenic microorganisms possibly present such as Staphylococcus aureus, Salmonella sp., Clostridium botulinum, C. perfringens, C. chauvoei Campylobacter sp., Escherichia coli, and Corynebacterium sp. The experiment was conducted at the School of Agrarian and Veterinarian Sciences of Jaboticabal, - UNESP. Fecal samples were collected from the aviary. A fully randomized experimental design was used with 7 treatments and 4 replications, for a total of 28 samples. A decrease in total number of microorganisms was detected when treatment T0 (zero days of storage) was compared with treatment T6 (42 days of storage), with oscillations in numbers being observed during this period of time. Pathogenic bacteria such as Clostridiu noyvi, C. perfringens, C. sordelli, C. septicum and C. noyvi type B were detected, as well as non-pathogenic bacteria such as Bacillus sp. and Staphylococcus epidermidis.